In vitro Propagation of Solanum capsicoides All. An Important Therapeutic Agent 'Kantakari' (Plant Tissue Culture and Biotechnology, 2011)
Shoot tip explants from in vitro germinated seedlings of Solanum capsicoides All. inoculated on MS containing 2 mg/l BA produced maximum shoot induction response (26 shoots per explant). Rooting of the microshoots (19.4 roots per explant) was obtained better in half strength of MS supplemented with NAA (0.5 mg/l). Well rooted plantlets were successfully hardened with 80 per cent survival rate.   Key words: Solanum capsicoides, Propagation, Therapeutic agent   D.O.I. 10.3329/ptcb.v20i2.6912   Plant Tissue Cult. & Biotech. 20(2): 179-184, 2010 (December)